2005
DOI: 10.1248/bpb.28.1527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Activity of Piper solmsianum C. DC. var. solmsianum (Piperaceae)

Abstract: The incidence of opportunistic fungal infections in immunocompromised patients, such as those undergoing treatment with immunosuppressive drugs, intensive chemotherapy, AIDS patients and neonates, is increasing at an alarming rate. 1,2) These mycoses are very difficult to eradicate, and present an enormous challenge for healthcare providers. 3,4) The diversity of plant species in Brazil, together with their known ethnopharmacological uses, creates enormous potential for finding new structures with antifungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 30 publications
(39 reference statements)
4
47
2
6
Order By: Relevance
“…Spots were visualized under UV light or with sulfuric anisaldehyde, indicative of steroids and terpenes. 1 H NMR spectra were recorded at 300 MHz and…”
Section: General Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Spots were visualized under UV light or with sulfuric anisaldehyde, indicative of steroids and terpenes. 1 H NMR spectra were recorded at 300 MHz and…”
Section: General Proceduresmentioning
confidence: 99%
“…The search for new medicinal agents against the genera Microsporum and Trichophyton is very important because they are the main agents responsible for dermatophytoses, which are among the most common infectious diseases worldwide and require appropriate treatment (1,2). Vetiveria zizanioides (Linn.)…”
mentioning
confidence: 99%
“…Phytochemical studies revealed the presence of monoterpenes, sesquiterpenes, arylpropanoids, phenylpropanoids, lignans and neolignans, most of which showing biological activity against bacteria, fungus and the trypomastigote form of Trypanossoma cruzi (Moreira et al 1995;Martins et al 2000;Campos et al 2005;2007).…”
Section: Introductionmentioning
confidence: 99%
“…47 A substância 4, orientina 8-C-β-D-glucopiranosídeo, já foi previamente isolada de Piper solmsianum e P. lhotzyanum. 47,48 Derivados C-glicosilados da vitexina, tais como a vitexina-C-α-Lraminose-(1→2)-β-D-glucopiranosídeo, vitexina-C-α-L-arabinosídeo e vitexina-C-β-glucopiranosídeo, foram descritos em Piper methysticum. 49 Entretanto, a vitexina 2"-O-β-D-glucopiranosídeo (2) está sendo descrita pela primeira vez neste gênero.…”
Section: Resultsunclassified